Approche de l’onomastique commerciale des écrits de la ville de Mostaganem : le cas des enseignes - Azzedine MALEK (My University, 2014)
Usually in the Algerian urban environment, we can see posters containing expressions and nouns which tell us about various occupations, trade activities, sanitary services (or any given agency), and which role is to offer resources and facilities to the customers. In order to understand the linguistic working of the urban environment through its writings, this study will mainly focus on authorized writings as opposed to unauthorized writings. It is worth pointing out that this dissertation falls under the framework of previous Canadian and French researches which dealt with both the graphic environment and the urban writings phenomena. Indeed, those pieces of research are regarded as significant references as our topic research precisely draws insights from social geography, urban sociology, onomastics and sociolinguistics. This leads us to raise some questions, notably, why can we find bilingual and/or trilingual posters? To which extent does the poster help in guiding the readers’ attention? In others terms, what are the elements which mostly attract the readers’ interest (colors, design, graphics, light and size of the poster, billboarding, etc.) ? What about the material aspect of the billboarding used by the scriptwriter to design the poster (writings and drawings on the walls, on the façade, wooden plates, metal-made materials, etc.)? Is the urban writings location considered as being a factor of linguistic variation (center of town vs. suburbs, residential vs. popular districts, etc.)? What are the functions performed by those same semiographic aspects in the Algerian graphic environment (For instance, the poster chromatics i.e. the color/product relationship, etc.)?
Keywords: urban sociolinguistics, commercial onomastics, commercial posters, stroller, graphic environment.